Antlions of southern Africa: genus Crambomorphus McLachlan, 1867, including extra-limital species (Neuroptera: Myrmeleontidae: Palparinae: Palparini) - Mansell, Mervyn W. (Zootaxa, 2018)
The genus Crambomorphus McLachlan, 1867, is revised. It now comprises six species, four from the western regions of southern Africa and two from Madagascar. Two new species, C. kalaharicus and C. namibicus, are described and illustrated, and a new combination is proposed for Palpares karrooanus Péringuey. Larvae of the two new species are described and illustrated.